Child-Langmuir law for cathode sheath of glow discharge in CO₂ - Lisovskiy, V.A.; Krol, H.H.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2017)
This work is devoted to the determination of the law that may be applicable to the description of the cathode sheath in CO₂. To this end three versions of the Child-Langmuir law have been considered – a collision free one (for the ions moving through a cathode sheath without collisions with gas molecules) as well as two collision- related versions– one for a constant mean free path of positive ions and one for a constant mobility of positive ions. The current-voltage characteristics and the cathode sheath thickness of the glow discharge in СО₂ have been simultaneously measured in the pressure range from 0.05 to 1 Torr and with the discharge current values up to 80 mA. In the whole range of the discharge conditions we have studied the cathode sheath characteristics are found to obey correctly only to the Child-Langmuir law version with a constant ion mobility. Данная работа посвящена определению закона, который может применяться для описания катодного слоя в CO₂. Выполнен анализ трёх законов Чайльда-Ленгмюра – бесстолкновительного (для движения ионов через катодный слой без столкновений с молекулами газа), а также двух столкновительных – с постоянными длиной свободного пробега и подвижностью положительных ионов. Для этого были одновременно измерены вольт-амперные характеристики и толщина катодного слоя тлеющего разряда в СО₂ в диапазоне давлений от 0,05 до 1 Торр и разрядных токов до 80 мА. В результате получено, что во всём исследованном нами диапазоне разрядных условий характеристики катодного слоя корректно описываются только законом Чайльда-Ленгмюра с постоянной подвижностью ионов. Ця робота присвячена визначенню закону, який може застосовуватися для опису катодного шару в CO₂. Виконано аналіз трьох законів Чайльда-Ленгмюра – для руху іонів крізь катодний шар без зіткнень з молекулами газу, а також законів з постійними довжиною вільного пробігу і рухливістю позитивних іонів. Для цього були одночасно виміряні вольт-амперні характеристики і товщина катодного шару тліючого розряду в СО₂ в діапазоні тиску від 0,05 до 1 Торр і розрядних струмів до 80 мА. У результаті отримано, що в усьому дослідженому нами діапазоні розрядних умов характеристики катодного шару коректно описуються тільки законом Чайльда-Ленгмюра з постійною рухливістю іонів.